eShadow LCE: Evolution of a Digital Shadow Theatre Platform to Support Analog Puppet Digitization and Collaboration - Ioannidis, Christos; Moumoutzis, Nektarios; Christoulakis, Marios (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
Shadow theatre is a culturally significant storytelling tradition that has evolved across centuries, with Greek “Karagiozis” standing out as a prominent example that blends humor, social commentary, and historical reflection. Despite its cultural value, the art form faces decline in the digital age. This is in sharp contrast to its educational potential to foster creativity, collaboration, and cultural awareness. Modern digital technologies offer promising solutions to help revitalize shadow theatre and make it accessible across schools to enable rich learning experiences. This paper presents eShadow LCE, an enhanced digital shadow theatre platform that supports real‑time collaboration, simplified puppet creation through mobile‑based computer vision and AI, and an inclusive methodology for classroom use. Used within the Stories4All Erasmus+ project, eShadow LCE was evaluated during a three‑day teacher training event focused on digital storytelling, empathy, and inclusion. Findings from participant feedback and a standard user experience questionnaire demonstrate the platform’s strong usability and educational value.